Florística e fitossociologia de Cerrado Sentido Restrito em regeneração natural no município de Pirassununga, estado de São Paulo - Leal, Thiago de Souza [UNESP] (2015)
The Cerrado is a well known center of plant diversity that is under severe human pressure, and the high potential for natural regeneration is an important feature of its vegetation. This study aimed to investigate the floristic composition and the phytosociological structure of Cerrado strictu sensu area in natural regeneration process in the municipality of Pirassununga, São Paulo, Brazil. The area belongs to the campus of the University of São Paulo (USP) found in the reference coordinates 21°56'25S e 47°28'17W. The fragment holds 88 ha of a well-developed secondary vegetation recovered after human impact to 40 years ago For the phytosociological study, based on the chronology of the last 30 years, we allocated 82 samples (20 x 10 m) over three transects, in which all individuals with PAP≥ 10 cm were sampled, with their PAS also measured. The botanical material was herborized and registered in the Hebarium Rioclarense (HRCB). The sample sufficiency was verified by the species accumulation curves. Usual phytosociological parameters (density, frequency, dominance and importance value) were provided together with others related analyses. There was Principal Coordinates Analysis (PCoA) and dendrogram for comparison with other areas of Cerrado. We sampled 5240 individuals, representing 100 species and 41 families. The density and basal area estimated were 3195.7 ind.ha-1 and 19.6 m2.ha-1, respectively. The diversity index (H') found was 3.062 nats.indivíduos-1 with equability (J') equal to 0.668. The richest families were Fabaceae (fifteen species), Myrtaceae (nine), Vochysiaceae (six), the richest genera are Myrcia (six species), Byrsonima, Erythroxylum, Miconia and Qualea (three each) and the most important species Xylopia aromatica, Qualea grandiflora, Miconia albicans, Vochysia tucanorum and Myrcia guianensis. The area of Cerrado sensu stricto in regeneration studied holds a good number of species, diversity index and a ...